The Effect of Work Environment and Behavior on Health Complaints in Female Waste Pickers at Terjun Landfill - Ferusgel, Agnes; Nasution, Rina Mahyurni; Tarigan, Yenni Gustiani (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Background: Nowadays, female workers are vulnerable to workplace hazards. One of the groups who are highly vulnerable to the exposure of workplace hazards is female waste pickers. This study focused on breathing problems in female waste collectors. The present study aimed to determine the effect of work behavior and work environment on respiratory complaints in female waste pickers at Terjun Landfill in Medan City. Methods: It was a cross sectional study in which the independent variables were work behavior and work environment, while the dependent variable was health complaints, respiratory complaints in particular. Work behavior was measured by collecting the data of protective mask use, while the data of work environment was collected by exploring the concentration level of CH4 and H2S at Terjun Landfill in Medan City. A total of 53 female waste pickers were participated as research sample. The data was analyzed by performing multiple linear regression calculation. Conclusion: It was obtained that there was an effect of work behavior (p=0.047) and concentration level of CH4 (p= 0.000) on respiratory complaints in female waste pickers at Terjun Landfill. However, it was found that H2S concentration level did not have an effect on respiratory complaints in female waste pickers at Terjun Landfill in Medan City. This study suggests that Sanitary and Park Office of Medan City can work together with related stakeholders to cultivate methane emissions (CH4) to become energy source to reduce air pollution at waste landfill, whereas to female waste collectors, this study suggests that they can regularly use protective mask to minimize the risk of hazardous gas at workplace.